2017
DOI: 10.1002/jsfa.8231
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of combination of calcium propionate and chitosan for preserving minimally processed banana quality

Abstract: BACKGROUND The marketability of fresh‐cut banana slices is limited by the rapid rate of fruit softening and browning. However, there is no scientific literature available about the role of postharvest calcium propionate and chitosan treatment on the quality attributes of fresh‐cut banana. Therefore, the aim of the present study was to investigate these effects. RESULTS The application of calcium propionate plus chitosan (CaP+Chit) retained higher firmness, higher ascorbic acid content, higher total antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Although there were oscillations in the enzymatic activity in apples treated with the antioxidant solutions, the PPO activity of these treatments was lower than the activity observed under the CT. Similar results were observed by Mirshekari et al, (2017) when working with MP 'Berangan' bananas treated with calcium propionate and chitosan. Even without major differences in POD and PPO activity among antioxidant treatments, LC and EA (1 %, 2 % and 3 %), the phenolic substrates were preserved as previously shown.…”
Section: Resultssupporting
confidence: 82%
“…Although there were oscillations in the enzymatic activity in apples treated with the antioxidant solutions, the PPO activity of these treatments was lower than the activity observed under the CT. Similar results were observed by Mirshekari et al, (2017) when working with MP 'Berangan' bananas treated with calcium propionate and chitosan. Even without major differences in POD and PPO activity among antioxidant treatments, LC and EA (1 %, 2 % and 3 %), the phenolic substrates were preserved as previously shown.…”
Section: Resultssupporting
confidence: 82%
“…However, some foodborne pathogens that threaten human health are capable of surviving under refrigeration. Extensive supplementary methods to refrigeration have been applied, such as chemical‐based methods (chlorine and chlorine‐related compounds, calcium salts, organic acids) (Gomez‐Lopez et al ., 2009; Mirshekari et al ., 2017; Ali et al ., 2020), use of plant essential oils (Tao et al ., 2019), modified atmospheric packaging (Fan et al ., 2019), edible coatings (Sarengaowa et al ., 2017) and UV‐C treatment (Zhang et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Calcium chloride and ascorbic acid together exhibit a synergistic effect in the prevention of browning and softening (Danyen et al., 2009). Calcium impedes the softening by chelating with the pectin, also, the coating of chitosan with calcium propionate increases the firmness of the slices by 2.3 times (Mirshekari et al., 2017). Recently, a study concluded that a gum based coating provided a shelf life of 21 days at 13 °C (Shahbazi & Shavisi, 2020).…”
Section: Pre‐processed Fruits and Their Process Conditionsmentioning
confidence: 99%